Cloning and expression of the nucleocapsid protein gene of Nipah virus in different strains of Escherichia coli - Ong, S.T.; Tan, W.S.; Hassan, S.S.; Mohd Lila, M.A. (Taylor & Francis, 2002)
The coding region of the nucleocapsid (N) gene was amplified from the viral RNA and inserted into the bacterial expression vector, pTrcHis2, for intracellular expression in three Escherichia coli strains: TOP 10, BL 21 and SG 935. The N protein was expressed as a fusion protein containing the myc epitope and His-tag at its C-terminal end. The amount of the fusion protein expressed in strain SG 935 was significantly higher than the other two strains, and was detected by the anti-myc antibody, anti-His and swine anti-NiV serum. Hence, the Nfus protein produced in E. coli could serve as an alternative antigen for the detection of anti-NiV in swine.